ANALISIS NILAI MORAL DALAM FILM HARAKIRI TAHUN 1962 KARYA MASAKI KOBAYASHI: PERSPEKTIF KRITIK TERHADAP SISTEM FEODAL JEPANG - Putra, Dandi Kelana; Isnaini, Zuli Laili; Nasution, Yenny Aristia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study analyzes the moral values contained in the film Harakiri (1962) by Masaki Kobayashi, focusing on its critique of the Japanese feudal system. The film highlights the story of Hanshiro Tsugumo, a ronin who questions the concepts of honor and justice within a rigid feudal society. Using a descriptive qualitative analysis method, this study identifies and examines key moral values such as justice, humanity, social responsibility, and criticism of the hypocrisy within the feudal system. The analysis reveals that Harakiri not only questions bushido as a moral guide but also exposes the injustices and powerlessness of individuals under an inhumane social hierarchy. The film suggests that true honor does not come from blind obedience to rules but from the courage to uphold human values. Thus, this research contributes to the understanding of social criticism in Japanese cinema, particularly concerning moral values that stand in opposition to a repressive social system.Key Words: Moral Values, Bushido, Feudalism, Harakiri, Social Criticism